The Impact of Military Allocations on Economic Development: Insights from the South Caucasus Region - Hasanov, Ramil I.; Rustamov, Tural; Alibeyli, Aziz; Huseynova, Emiliya; Safarli, Arzu (International Journal of Economics and Financial Issues, 2025)
The shifting geopolitical landscape, along with ongoing global political changes, necessitates a comprehensive reassessment of military expenditures within national governance frameworks. The South Caucasus region, characterized by complex and enduring geopolitical challenges stemming from centuries of military conflict, serves as a critical case for this exploration. This study investigates the role of military spending within the region’s political and economic frameworks, focusing on its impact on economic growth and military capabilities. Specifically, it analyzes the relationship between military expenditure and GDP per capita in Azerbaijan, Armenia, and Georgia, employing the Granger causality test for the period from 1996 to 2022. The empirical results show a bidirectional causality between military expenditure and GDP per capita in Azerbaijan, indicating a reciprocal relationship between these variables. In contrast, both Armenia and Georgia exhibit unidirectional causality, where economic growth influences military spending, suggesting that economic performance is a key determinant in defense budgeting decisions in these countries. Beyond econometric analysis, the study incorporates an ethical perspective, exploring how military spending, shaped by factors such as geopolitical pressures, technological innovations, and security concerns can influence economic development. By examining the broader implications of military budgets on national identity, sovereignty, and regional stability, this research offers valuable insights for policymakers.